1. The problem statement, all variables and given/known data Find g(x) if f(x) = (3x-1)/(2x+5) and f(g(x)) = (x+9)/(12x-11) 2. Relevant equations N/A, as far as I know 3. The attempt at a solution I tried doing it as though g(x) = y and it turned out like this: (3y-1)/(2y+5)=(x+9)/(12x-11) I very quickly saw that that wouldn't work though, so I'm kind of lost. This is independent work in order for me to be able to go into pre-calc, so while I can ask a teacher it is difficult to find time, hence why I'm relying on you guys :) Help would be much appreciated!